Pengaruh Metode Pembelajaran Musikal bagi Kemampuan Kognitif Anak Autis di SLB Negeri Manekat Niki-Niki - Erli Njudang; Yulius Yusak Ranimpi; Iky Sumarthina Putri Prayitno (Universitas Negeri Yogyakarta, 2020)
Cognitive ability is one of the important aspects for individuals who need to be equipped and developed since childhood, including children with autism. Children with autism have difficulty receiving and understanding learning material and information received in class because they have problems with cognitive abilities. Therefore, we need a new learning method that is expected to help children with autism in developing their cognitive abilities to support learning activities in the classroom. This research aimed to determine the effect of musical learning methods on the cognitive abilities of autistic students. The subjects were 3 autistic students who experience obstacles in composing language in communication, difficulty of concentrating, and behaving repetitively in SLB Negeri Manekat Niki-Niki. The research method used was pre-experimental design quantitative with one group pretest-posttest design. The data analysis technique used was descriptive statistical analysis. The results showed that musical learning methods were effective and had an effect on the cognitive abilities of autistic students who had limitations in concentrating and repetitive behavior, but were not yet effective enough for autistic students who had language development disorders in communication.